1981
DOI: 10.1002/ajh.2830110203
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of enzymes of erythrocytes from newborn infants and adults: Activity, thermostability, and electrophoretic profile as a function of cell age

Abstract: THe level of enzyme activity, the enzyme thermostability profile, and the isozyme electrophoretic pattern were determined in young and old erythrocytes from newborn infants and adults and in samples from adult individuals with increased reticulocyte counts. Cord blood samples had higher levels of enzymatic activity for 12 of the 14 enzymes measured, adenylate kinase and phosphoglucomutase being the exceptions. The largest differences in activity between newborns and adults were for glutamic oxaloacetic transam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
2

Year Published

1981
1981
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
(16 reference statements)
1
24
0
2
Order By: Relevance
“…The levels of enzyme activity and the cord blood to the adult blood activity ratios were similar to those in previous reports (10,13). The higher enzymatic activities in umbilical cord blood samples, for all enzymes except adenylate kinase, generally reflect differences in mean red cell age and percentage of reticulocyte between adult and cord blood samples, although they may also reflect unique characteristics of fetal erythrocytes (e.g., GPI), (14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of enzyme activity and the cord blood to the adult blood activity ratios were similar to those in previous reports (10,13). The higher enzymatic activities in umbilical cord blood samples, for all enzymes except adenylate kinase, generally reflect differences in mean red cell age and percentage of reticulocyte between adult and cord blood samples, although they may also reflect unique characteristics of fetal erythrocytes (e.g., GPI), (14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION Abnormal enzyme activities in erythrocytes may be due to several causes in addition to a structural alteration involving a single enzyme locus. Most ofthese causes, including changes in mean cell age or cell type (15,16), exposure to cytostatic drugs (22), and other dyserythropoietic conditions (23,24) usually result in alterations in the activity of several enzymes simultaneously and usually involve both increases and decreases in activity. Therefore, it is unlikely that an acquired enzymopathy would fulfill our requirement that the level of enzymatic activity for eight of the nine enzymes assayed be within the normal range (excluding the G6PDA-variant).…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous-deficient individuals usually have 3-20% of normal TPI activity; all of this activity is heat labile, suggesting that at least one allele encodes a structurally altered protein (3, 9, 10). The other allele is presumably null, since mutations producing no detectable enzyme activity or immunologically cross-reacting material are by far the most prevalent abnormality affecting the human TPI locus (11)(12)(13)(14)(15).In the present study, we have determined the nucleotide sequence of two TPI alleles, each of which was isolated from unrelated individuals homozygous for TPI deficiency. Relative to a normal allele (16), each allele harbors a single base pair change.…”
mentioning
confidence: 99%
“…Homozygous-deficient individuals usually have 3-20% of normal TPI activity; all of this activity is heat labile, suggesting that at least one allele encodes a structurally altered protein (3,9,10). The other allele is presumably null, since mutations producing no detectable enzyme activity or immunologically cross-reacting material are by far the most prevalent abnormality affecting the human TPI locus (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Wurzinger and Mohrenweiser (1982) reported that cord blood erythrocyte GOT1 activity was 1.3 times the activity in erythrocyte from pregnant females, 1.5 times the activity in non-pregnant females and 2.0 times the activity in males. The cord blood-adult blood disparities were thought to be related to cell age (Sass et al, 1964;Gahr et al, 1979;Mohrenweiser et al, 1981), while those between pregnant females and normal adults were related to increased vitamin B6 (pyridoxine) intake Jpn. Jo Human Genet.…”
Section: Resultsmentioning
confidence: 99%